USING REGRESSION ANALYSIS TO STUDY THE IMPACT OF CRUDE OIL SHOCKS ON THE PROFITABILITY OF THE BANKING SECTOR IN QATAR - Abdullah , Zana Najim; wali , Bashar natiq rashid; saber , Mustafa ahmed ezzulddin (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This study aims to analyze the impact of crude oil price shocks on the profitability of the banking sector in Qatar. The research focuses on a sample of four banks listed on the Qatar Stock Exchange during the period from 2005 to 2023. Using an econometric model based on the Ordinary Least Squares (OLS) method, The research investigates the impacts of oil price fluctuations. GDP growth, and loan loss provisions on return on assets (ROA), a metric used to quantify bank profitability. The results reveal that oil price shocks have a significant positive impact on bank profitability, highlighting the sector's dependence on oil revenues. Additionally, GDP growth positively influences profitability, while loan loss provisions show a negative effect. The study underscores the importance of diversifying income sources and improving credit risk management to enhance the resilience of the banking sector against oil price fluctuations.